Wspomnienia pośmiertne - CPH 3 (Czasopismo Prawno-Historyczne, 1951)
Koranyi Karol: Przemysław Dąbkowski (1877—1950) ... 474-476 Procházka Vladimir V.: Théodore Saturnik (1888—1949) ... 477-480 (en français)